The Impact of Credit Use on Rubber Farming Income in South Sumatra - Netti Tinaprilla; Harmini; Muhammad Farhan M. S (Jurnal AGRISEP, 2025)
Indonesian rubber plantations are experiencing a fluctuating productivity trend due to difficult capital access, which is one of the problems faced by farmers. Agricultural credit serves as an alternative solution to this issue. Financial credit serves as a solution to address the capital issues faced by farmers, as the additional capital from credit can be used to enhance input utilization, thereby optimizing production. This research aims to analyze the impact of credit use on rubber farming in South Sumatra Province. This research uses secondary data, specifically the 2014 Agricultural Household Survey data from the Central Statistics Agency. The respondent farmers totaled 4,924 rubber farmers in South Sumatra, consisting of 98 farmers who took credit and 4,826 farmers who did not take credit. South Sumatra was chosen as the research location because it is the province with the largest natural rubber production in Indonesia. The methods used were the descriptive method and propensity score matching (PSM) to assess the impact of credit on rubber farming income. The results showed that the largest expense for rubber farming in South Sumatra was the labor cost component within the family, indicating that rubber farming in South Sumatra remains labor-intensive. The allocation of credit funds that has not yet been accurately targeted in agriculture as a whole is a factor contributing to the insignificance of credit in increasing farmers income. Therefore, there is a need for extension services related to financial literacy so that credit funds can be optimized in agricultural practices.